PEREMPUAN KANAAN DAN DAYA JUANGNYA: SEBUAH TINJAUAN NARATIF ATAS MATIUS 15:21-28 DAN RELEVANSI TEOLOGISNYA BAGI PENDIDIKAN KARAKTER KRISTIANI - Samosir, Bofry Wahyu; Dirgaprimawan, Bernadus (Lembaga Penelitian STKIP Widya Yuwana, 2023)
This article aims at examining a fighting spirit that characterizes the Canaanite woman in Matthew 15:21-28 as a source of inspiration for Christian education addressed to the youth. It focuses on her choice of actions and of words, especially shown in verses 25 and 27. In order to do so, it employs a narrative method that takes seriously every detail related to her performance. It tries to understand how her struggle emerges and why Jesus says that she has a great faith. After discussing the subject matter in several points, this article comes to a conclusion that the element of faith first of all lies on the human side, namely a fighting spirit, a spiritual entrance to receive God's mercy. Pope Francis states that a fighting spirit is visible when Christian believers, especially young people